A new large-flowered odontoglossum (orchidaceae: oncidiinae) from the Cusco region in Peru - Dalström, Stig (Universidad de Costa Rica, 2014)
Plants of a colorful Odontoglossum were recently found by separate parties in the Cusco region of central Peru. The species was incorrectly identified as Odontoglossum epidendroides, independently by both parties. Although similar in appearance, a closer examination of the flower reveals that it represents a new species, which is scientifically described here and compared with similar species. The new taxon is distinguished from the similar O. cruentum and O. juninense by morphological features of the column, such as the lateral curvature profile, with larger and more rectangular wings, and in combination with the well developed falcate callus structure on the lip. Our new species is also distinguished from the rather similar O. epidendroides by having flowers with a shorter column with shorter wings.